Body mass index, waist circumference and waist:hip ratio as predictors of cardiovascular riska review of the literature - Huxley, Rachel; Mendis, S.; Zheleznyakov, E.; Reddy, S.; Chan, J. (Nature Publishing Group, 2010)
Overweight and obesity have become a major public health problem in both developing and developed countries as they are causally related to a wide spectrum of chronic diseases including type II diabetes, cardiovascular diseases and cancer. However, uncertainty regarding the most appropriate means by which to define excess body weight remains. Traditionally, body mass index (BMI) has been the most widely used method by which to determine the prevalence of overweight in, and across, populations as well as an individual's level of risk. However, in recent years, measures of central obesity, principally waist circumference and the waist:hip ratio and to a lesser extent the waist:height ratio, which more accurately describe the distribution of body fat compared with BMI, have been suggested to be more closely associated with subsequent morbidity and mortality. There is also uncertainty about how these measures perform across diverse ethnic groups; earlier, most of the evidence regarding the relationships between excess weight and risk has been derived chiefly from Caucasian populations, and hence, it remains unclear whether the relationships are consistent in non-Caucasian populations. The purpose of this review, therefore, is to provide an overview of the current evidence-base focusing predominantly on three main questions: (1) Which, if any, of the commonly used anthropometric measures to define excess weight is more strongly associated with cardiovascular risk? (2) Which of the anthropometric measures is a better discriminator of risk? and (3) Are there any notable differences in the strength and nature of these associations across diverse ethnic groups? © 2010 Macmillan Publishers Limited All rights reserved.